Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Berbantuan Multimedia pada Mata Pelajaran IPAS Terhadap Hasil Belajar Siswa Kelas IV SDN Ungkaya - Cahyani, Intan Tri; Kaharu, Sarintan N.; Rahma, Nur (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
Natural and Social Sciences Learning (IPAS) aims to develop students' ability to understand and apply scientific and social concepts in daily life, as well as to improve their scientific and social literacy. However, the reality is that there are still many students who have difficulty understanding the material and are less interested in science subjects, especially in science material. This study aims to determine the influence of the multimedia-assisted Contextual Teaching and Learning (CTL) model on student learning outcomes in Natural and Social Sciences (IPAS) subjects in grade IV of SDN Ungkaya. The research method used was a quasi-experiment (Quasi Experiment) with a Nonequivalent (Pretest and Posttest) Control Group Design. Data analysis uses prerequisite tests, namely, normality test and homogeneity test as well as hypothesis testing using the Independent Sample T-test and N-gain test assisted by the SPSS version 30 program. The results showed that there was a significant influence of the multimedia-assisted Contextual Teaching and Learning (CTL) model on student learning outcomes, with the Independent sample T-Test Two-Sided test score p = 0.019. The results of the T-Test showed that the significance value of Two-Sided p < 0.05. The results of the study also showed an average N-gain value of 0.7524 which was categorized as high effectiveness. It can be concluded that the multimedia-assisted Contextual Teaching and Learning (CTL) model is effective and can have a positive effect on student learning outcomes.